Approaching transfer learning to identify correctly worn facial masks - Sadid, Tausif; Hossain, Md Sadik; Sengupta, Sudip Kumar; Khondaker, Serazam Munira (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.